The Role Of Human Resources In Sea Transport Safety And Security: Literature Review - Taharuddin; Isnen Fitri; Rudy Susanto; Badaruddin; Satia Negara Lubis; Tasdik Tona (Meteor STIP Marunda, 2024)
Humans play an important role in maintaining the safety and security of lives on board ships. Most of the causes of accidents in the shipping sector are human elements. Improving shipping and navigation safety can be done by strengthening and focusing on human factors. Approximately 80% of world trade is on sea routes so that the safety and security of lives at sea and the protection of the marine environment are highly dependent on the professionalism and competence of a sailor. The study will focus on human resource governance issues that are very important in the planning and operation of marine transportation systems. Marine environmental safety is one of the focuses studied in this study. The study aims to determine the role of humans in improving safety and security in marine transportation systems by using variables of improving vocational college institutions, improving sailor competence and improving the propriety of operators and users of marine transportation services. The approach taken in this study is the literature review method and observation of problems and cases of accidents in marine transportation as well as interviews with several academics and practitioners who have experience in the world of shipping. The results of this study provide a comprehensive picture of the contribution of human resources in reducing accidents and maintaining the sustainability of the maritime environment in the marine transportation system by strengthening the institutional system of educational and training institutions in improving the professionalism and competence of marine transportation human resources.